Indentifikasi Pasar, Segmen Dan Target Pasar Sasaran Bisnis Asuransi - Habib Bayhaqi; Nuri Aslami (Yayasan Literasi Sains Indonesia, 2022)
To achieve the still-small target of insurance participants in Indonesia, as well as the potential benefits of market and company segmentation, empirical research into consumer needs and desires, as well as a management system capable of adapting business processes to these needs and desires, are required. Consumers in target sharia insurance participants make purchases based on the advantages offered or the potential of items and services to assist them in solving a specific problem. Companies might provide a wide range of items and services, but customers only purchase advantages or solutions to issues that the products and services in question provide.